Aplicação de coagulantes naturais e químicos para tratamento do efluente de indústria de curtimento de couro - Silva, Gustavo de Souza (2014)
The leather tanning industry utilises large amount of toxic substances and water, thus generating effluents that have high pollution load, with high chemical oxygen demand, colour, presence of dissolved salts and many metals. Due to the large amount of effluent generated by tanneries and the difficulty in their treatment, several studies have been proposed to minimize the environmental impacts caused by inappropriate disposal of this effluent. This study investigated the performance of natural coagulants Moringa oleifera and Tanfloc compared to chemical coagulants aluminium sulphate and ferric chloride commonly used in the treatment of raw wastewater from tannery, by means of the physicochemical processes of coagulation, flocculation and sedimentation. Utilising jar tests, different concentrations for the coagulants (chemical and natural) were applied to the concerned effluent and it was assessed their efficiency in removing certain parameters such as pH, colour, electrical conductivity, COD, and total, fixed and volatile solids. The results showed that for pH and electrical conductivity parameters, there was no significant variation after application of coagulant in relation to the raw effluent, since pH values remained very alkaline and electrical conductivity with high salts concentration. By comparing the coagulants for colour parameter it was observed that the natural coagulant Tanfloc had greater efficiency compared to the chemical ones, reaching 56.9% of removal, however, the aluminium sulphate was more efficient at removing COD, with 95% of removal, and also at removing fixed and volatile solids, with efficiency higher than 70%. Therefore, it is noticed that the chemical coagulant aluminium sulphate was more successful for the majority of the analysed parameters in comparison to other coagulants.